Pericardial mesothelioma in a German Shepherd dog: a case report - Ceribasi, S.; Ozkaraca, M.; Ceribasi, A. O.; Ozer, H. (Czech Academy Agricultural Sciences, 2013)
In this case report, a diagnosis of pericardial mesothelioma in a four year old male German shepherd dog is described. The dog, which had anorexia, bloody diarrhoea, dehydration and depression and, died on day 10 of therapy, was systematically necropsied. At necropsy, approximately 1.5 litres of cloudy and bloody exudate were detected in the thoracic cavity. The parietal lamina of the pericardium was covered with multilobular nodular masses related with each other, 1 to 5 cm in diameter and grey-yellow in colour. There were proliferations characterised with grey-yellow colour and approximately 1 to 5 mm in length on visceral pleura. The presence of abscess foci with liquefied-centrum was observed when examining a section surface of the lung. The appearance of the oesophageal serosa, thoracic aorta and the thoracic section of the diaphragm were similar to pleura. A thickening was microscopically determined in the parietal lamina of the pleura and pericardium due to papillary proliferations consisting of cells similar to cubic or cylindrical epithelium. Severe lymphocyte and plasma cell infiltrations were observed in the pleural sections next to the lung. Neoplastic cells had nuclei with large eosinophilic granular cytoplasms and large vesicular and single nucleoli. Some neoplastic cells were determined to include intracytoplasmic vacuoles. The neoplastic cells contained some mitotic figures. It was observed that some tumour cells contributed to giant cell formation through integration. In periodic acid Schiff-haematoxylin ( PAS-H) examinations it was determined that the pleural basal membrane maintained its integrity. Immunohistochemically, the tumour gave a weak positive reaction with anti-pancytokeratin staining while giving intense reaction with anti-vimentin staining.
Keywords: dog; mesothelioma; pericardium